Characterization of the complete chloroplast genome sequence of Hemsleya zhejiangensis (cucurbitaceae), a rare and endangered wild plant species in Zhejiang province, China - Yanrong Li; Jinghui Li; Lingli Fang; Ming Jiang (Mitochondrial DNA. Part B. Resources, 2019)
Hemsleya zhejiangensis is a rare and endangered plant species which is listed as a key protected wild plant in Zhejiang province, China. In our present study, we assembled the complete chloroplast (CP) genome of H. zhejiangensis using high-throughput sequencing data. The whole genome sequence of H. zhejiangensis is 157,289 bp in size, with a GC content of 37.1%. Sequencing analyses reveal that the CP genome encodes 133 genes, including 84 protein-coding genes, 8 rRNA genes, 37 tRNA genes, and four pseudogenes. Phylogenetic analysis results indicate that H. zhejiangensis is clustered with H. lijiangensis, with a support value of 100%, and they are sister to the three Gynostemma species.